ANALYSIS OF INVESTMENT FEASIBILITY IN BROILER CHICKEN FARMING INSTRUMENTS IN KARAN BAYAT VILLAGE - Misrul; Rusmini (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to analyze the investment feasibility of broiler chicken farming in Karan Bayat Village, a region with high potential in the poultry agribusiness sector. A descriptive qualitative approach was used, with data collected through in-depth interviews, field observations, and document studies involving farmers, village officials, and related business actors. The results show that broiler chicken farming in the village is dominated by small to medium-scale businesses, employing two main rearing systems: independent and partnership-based. Key factors determining investment feasibility include feed prices, fluctuations in chicken selling prices, financial management, access to financing, and poultry disease risks. Most farmers perceive this business as profitable and feasible to develop, especially with good management and external support from the government and financial institutions. The study recommends strengthening business management, developing fair partnerships, and improving capacity and infrastructure as strategies to enhance competitiveness and investment sustainability.